2015
DOI: 10.1103/physreve.91.013306
|View full text |Cite
|
Sign up to set email alerts
|

Idle waves in high-performance computing

Abstract: The vast majority of parallel scientific applications distributes computation among processes that are in a busy state when computing and in an idle state when waiting for information from other processes. We identify the propagation of idle waves through processes in scientific applications with a local information exchange between the two processes. Idle waves are nondispersive and have a phase velocity inversely proportional to the average busy time. The physical mechanism enabling the propagation of idle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Data communication modeling in high-performance computing is a subject of constant development 50,51 . In particular for message-passing parallel programming models where blocking, as well as, nonblocking communications while synchronizing nearest-neighbor processes affect the performance of the simulations 52 .…”
Section: A Modeling and Scaling Laws For Hespaddamentioning
confidence: 99%
“…Data communication modeling in high-performance computing is a subject of constant development 50,51 . In particular for message-passing parallel programming models where blocking, as well as, nonblocking communications while synchronizing nearest-neighbor processes affect the performance of the simulations 52 .…”
Section: A Modeling and Scaling Laws For Hespaddamentioning
confidence: 99%
“…Previous works on simulations of idle period propagation showed that idle period propagates among processes in certain point-to-point communication patterns such as neighbor communication [1] and collective operations [3]. LogGOPSim simulations [4] predicted that idle periods propagate among MPI processes as waves with a propagation speed depending on the average computational time and network parameters [1]. Montecarlo simulations showed that certain classes of collective operations have the property of hiding process imbalance and minimizing idle period propagation [3].…”
Section: Related Workmentioning
confidence: 99%
“…In a different work based on simulation results, [6] pointed out that both collective and point-to-point operations can impact the sensitivity of parallel applications to system noise and that the blocking communication mode has an amplification effect of system noise. Also based on simulation results, [1] presented an equation description of the propagation speed of idle waves in scientific applications on large number of processes.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations